IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH THINK PAIR SHARE STRATEGY - Umami - Handayani (TRANSFORM : Journal of English Language Teaching and Learning, 2014)
ABSTRACT This research is designed to improve the students’ reading comprehension in English through Think Pair Share strategy. the objective of the research is to develop Think Pair Share to improve the students’ reading comprehension. The research was  conducted by using  classroom action research. The finding showed that Think Pair Share strategy was successful in improving students’ reading comprehension. The improvement couls be seen from the increase of students’ reading scores. Besides, the finding also showed that Think Pair Share strategy was effective in enhancing the students’ participation, especially in term of sharing ideas, asking and answering questions. Keyword: Think Pair Share strategy, improve, reading comprehension